(untitled) (International Journal of Engineering and Computer Science, 2015)
Since WSN’s have seen tremendous growth in the past few years and have contributed in transforming the society from simple living to smart living. To explore the diverse deployments of WSN, we have studied the various practical deployment applications of WSN in this research work. For each deployment site, we studied its application credentials and technical details related to the deployment site. We feel that this study will not only provide the in-depth knowledge to the learning community, but we will also open the new area of research for rapid commercial deployment of the WSN.